2015
DOI: 10.1080/09168451.2014.955453
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obese and anti-diabetic effects of a mixture of daidzin and glycitin on C57BL/6J mice fed with a high-fat diet

Abstract: To cite this article: Yanqing Zang, Kiharu Igarashi & Changqing Yu (2015) Anti-obese and antidiabetic effects of a mixture of daidzin and glycitin on C57BL/6J mice fed with a high-fat diet,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Therefore, the actual bioactive compounds after DZ oral administration may likely be its metabolites other than DZ itself which will require further investigation. A recent study by Zang et al [15] demonstrated the positive role of the mixture of DZ and glycitin in decreasing blood glucose and serum HbA1c, which partly supported our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the actual bioactive compounds after DZ oral administration may likely be its metabolites other than DZ itself which will require further investigation. A recent study by Zang et al [15] demonstrated the positive role of the mixture of DZ and glycitin in decreasing blood glucose and serum HbA1c, which partly supported our findings.…”
Section: Discussionsupporting
confidence: 92%
“…However, Meezan et al [14] reported that intraperitoneal injection of DZ impaired glucose tolerance in ob/ob diabetic mice. Recently, Zang et al [15] demonstrated that the mixture of DZ and glycitin can efficiently decrease blood glucose and serum HbA1c in hyperglycemic mice. Although the mixture of DZ and glycitin were effective in the treatment of DM, the exact role of DZ was not distinguished in their report.…”
Section: Introductionmentioning
confidence: 99%
“…Another study with high fat diet fed C57BL/6J mice reported the synergistic effect of daidzein and glycitin (0.06% mixture in diet, in the ratio of 3:1) in controlling diabetes and obesity‐related complications. Results showed a significant reduction in body weight gain, fat content in adipose tissue, and the levels of fasting glucose, HbA1c, insulin, and total cholesterol . In a study of C57BL/6j lean mice using radio labeled (C 14 ) glucose, Meezan et al .…”
Section: Effect Of Daidzein On T2d Pathophysiologymentioning
confidence: 99%
“…which had many potential bioactive effects (Xu et al, 2002). It has been reported that it could induce anti-obesity and anti-diabetes effects on highfat diet mice (Zang et al, 2014). In our previous study, glycitin was shown to have a protective effect on UV-induced skin photoageing in human dermal fibroblasts (Seo et al, 2014).…”
Section: Introductionmentioning
confidence: 95%